2022
DOI: 10.3389/fpls.2022.1035573
|View full text |Cite
|
Sign up to set email alerts
|

Protein-protein interactions in plant antioxidant defense

Abstract: The regulation of reactive oxygen species (ROS) levels in plants is ensured by mechanisms preventing their over accumulation, and by diverse antioxidants, including enzymes and nonenzymatic compounds. These are affected by redox conditions, posttranslational modifications, transcriptional and posttranscriptional modifications, Ca2+, nitric oxide (NO) and mitogen-activated protein kinase signaling pathways. Recent knowledge about protein-protein interactions (PPIs) of antioxidant enzymes advanced during last de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 271 publications
0
6
0
Order By: Relevance
“…Reactive oxygen species (ROS) are components of multiple metabolic and developmental pathways in plants under normal and stress conditions [43]. At low concentrations, ROS perform signaling functions and are involved in regulating plant growth and development and plant response to stress.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) are components of multiple metabolic and developmental pathways in plants under normal and stress conditions [43]. At low concentrations, ROS perform signaling functions and are involved in regulating plant growth and development and plant response to stress.…”
Section: Discussionmentioning
confidence: 99%
“…Protein content is a vital component of the system that controls reactive oxygen species. The enzymes' folding, stability, degradation, and activation are controlled by proteins, and these processes have significant effects on ROS buildup and plant stress tolerance [70]. Compression has shown that total phenols (TPs) are active during the process of plant growth and play a significant positive role in the plant growth mechanism [71].…”
Section: Interpretation To Mgo Nps In Biochemical Characterizationmentioning
confidence: 99%
“…(2020) found a viral protein that moved from the plasma membrane to chloroplasts upon plant sensing of biotic threats, suggesting a protein‐mediated regulatory defence pathway linking the plasma membrane and chloroplasts. Moreover, protein–protein interactions such as folding, stabilisation, degradation and activation play important roles in ROS scavenging within diverse metabolic and physiological processes, but are understudied (Melicher et al ., 2022).…”
Section: Defence In the Symplastic Spacementioning
confidence: 99%